A Bias‐Free, Stand‐Alone, and Scalable Photovoltaic–Electrochemical Device for Solar Hydrogen Production. (12th May 2020) - Lee, Minoh; Turan, Bugra; Becker, Jan‐Philipp; Welter, Katharina; Klingebiel, Benjamin; Neumann, Elmar; Sohn, Yoo Jung; Merdzhanova, Tsvetelina; Kirchartz, Thomas; Finger, Friedhelm; Rau, Uwe; Haas, Stefan
Abstract: Although photovoltaic–electrochemical (PV–EC) water splitting is likely to be an important and powerful tool to provide environmentally friendly hydrogen, most developments in this field have been conducted on a laboratory scale so far. In order for the technology to make a sizeable impact on the energy transition, scaled up devices must be developed. Here a scalable (64 cm 2 aperture area) artificial PV–EC device composed of triple‐junction thin‐film silicon solar cells in conjunction with an electrodeposited bifunctional nickel iron molybdenum water‐splitting catalyst is shown. The device shows a solar to hydrogen efficiency of up to 4.67% (5.33% active area, H2 production rate of 1.26 μmol H2 /s) without bias assistance and wire connection and works for 30 min. The gas separation is enabled by incorporating a membrane in a 3D printed device frame. In addition, a wired small area device is also fabricated in order to show the potential of the concept. The device is operated for 127 h and initially 7.7% solar to hydrogen efficiency with a PV active area of 0.5 cm2 is achieved. Abstract : An upscaled (aperture area 64 cm 2 ) photovoltaic‐electrochemical device is demonstrated by continuous repetition of a completely self‐contained base unit. The base unit consists of a combination of triple junction a‐Si:H/a‐Si:H/μc‐Si:H solar cells and electrodeposited NiFeMo bifunctional water‐splitting catalyst. A bias‐free, stand‐alone, and scalable device shows solar to hydrogen efficiency of up to 4.67%.